Crimes against humanity in the context of the armed conflict in ukraine: definition, problems of distinction with related offences (Law and Safety, 2023)
The article is devoted to the characteristics of crimes against humanity as a category of international criminal law and in the context of the armed conflict in Ukraine. It has been stated that corpus delicti of crimes against humanity reveal many features which have a common meaning with the features of war crimes, and this creates difficulties in legal application. A table of the norms relevance and their drafts on crimes against humanity and war crimes under the Rome Statute of the ICC and the draft UN Convention on the Prevention and Punishment of Crimes against Humanity has been compiled. The criteria for distinction between these corpus delicti has been proposed. It has been established that the Criminal Code of Ukraine does not contain special corpus delicti of crimes against humanity. The conceptual direction of national criminal legislation improvement has been determined.